Bilateral versus unilateral upper limb training in (sub)acute stroke: A systematic and meta-analysis - Justine Dembele; Lisa Tedesco Triccas; Elogni Renaud Amanzonwé; Oyéné Kossi; Annemie Spooren (South African Journal of Physiotherapy, 2024)
Background: Integrating high dosage bilateral movements to improve upper limb (UL) recovery after stroke is a rehabilitation strategy that could potentially improve bimanual activities.